Investigating the Environmental and Health Problems Associated with Municipal Solid Waste in Bahawalpur City, Pakistan: Investigating the environmental and health problems associated with municipal solid waste - Mohsin, Muhammad; Khan, Asad Ali; Barkat, Tasleem (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2020)
Growing population and various economic activities in the cities has increased the generation of solid waste several times. Therefore, the main objective of the current research was to briefly investigate the impact of municipal solid waste on the environment and human health in Bahawalpur city. For this purpose, primary data about solid waste problems were collected using a structured questionnaire. Three hundred (300) respondents were asked from the residents of four study areas viz. Islami Colony, Model Town C, Model Town B, and Satellite Town (75 from each area) by applying simple random sampling. Necessary secondary data is collected from Bahawalpur Waste Management Company (BWMC). The analysis of the data was carried out in SPSS 17 by applying descriptive statistics, Pearson correlation, and a five-point Likert scale. Findings revealed that the problem is most aggravated in low-income areas (e.g. Islami Colony and Model Town C) where the performance of solid waste was counted average, poor, and very poor. Improper collection and disposal of solid waste also responsible for odour related problems mainly from waste throwing in open spaces like vomiting, land degradation, etc. This situation creates various environmental problems i.e. heaps of rubbish, dirty streets, flies and mosquitoes, and others. The ineffective management of solid waste was also creating severe diseases related to public health i.e. Malaria, respiratory problems, diarrhea, and others. The correlation results also highly significant and indicative that inadequate handling and throwing of solid waste creating severe environmental problems and diseases in the study areas.